2020
DOI: 10.1159/000505344
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 Variants rs1800977 (C69T) and rs9282541 (R230C) Are Associated with Susceptibility to Type 2 Diabetes

Abstract: Objective: Accumulated evidence suggests that ATP-binding cassette A1 transporter (ABCA1) contributes to secreting insulin in pancreatic β-cells and amyloid beta formation. This study aimed to investigate the association between three single nucleotide polymorphisms (SNPs) of ABCA1 and susceptibility to type 2 diabetes mellitus (T2DM) in a Han Chinese population. Methods: A total of 996 T2DM patients and 1,002 controls were included in the study. Three SNPs in the ABCA1 gene, i.e., rs2230806 (R219K), rs1800977… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Of these studies, 169 studies were excluded for the following reasons: data were on other polymorphisms ( n = 73); there was no ABCA1 polymorphism-grouped lipid outcome ( n = 52); there was no lipid outcome ( n = 19); the study was not a clinical trial ( n = 10); the sample size was less than 20 ( n = 8); the study involved children ( n = 4); there was an overlapping cohort ( n = 2); the study was not in English ( n = 1). Therefore, 18 articles were identified for this systematic review [ 13 , 14 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 169 studies were excluded for the following reasons: data were on other polymorphisms ( n = 73); there was no ABCA1 polymorphism-grouped lipid outcome ( n = 52); there was no lipid outcome ( n = 19); the study was not a clinical trial ( n = 10); the sample size was less than 20 ( n = 8); the study involved children ( n = 4); there was an overlapping cohort ( n = 2); the study was not in English ( n = 1). Therefore, 18 articles were identified for this systematic review [ 13 , 14 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…We detected in CR-WGS the ABCA1 variant rs9282541 that was considered a private variant in Native Americans and their descendants ( Villarreal-Molina et al, 2012 ; Du et al, 2020 ). Its allelic frequency resembles that observed in Latin Americans reported in 1KGP.…”
Section: Discussionmentioning
confidence: 99%
“…ABCA1 is involved in highdensity lipoprotein cholesterol (HDL-C) biogenesis, and changes in ABCA1 structure and/or protein expression could alter metabolic disturbances [17]. The loci of the ABCA1 gene rs2230806 is located in the major extracellular rings of the ABCA1 protein, which have an important role in APO-I and cholesterol efflux [18]. rs2230806 is also the most widely studied common missense polymorphism, and studies in Asians reported that ABCA1 SNP (rs2230806, also known as R219K or G1051A) is associated with type 2 DM and coronary heart disease [19,20].…”
Section: Introductionmentioning
confidence: 99%